Education unbound? Enlivening debates with a mobilities perspective on learning - Waters, J (SAGE Publications, 2016)
This paper contributes to recent debates on the geographies of education. I argue that research in geography on education over the past decade has conceptualised education principally in terms of attachment to - and boundedness within - particular (often institutional) places and spaces. Yet a productive tension has emerged in contemporary scholarship around the competing concepts of mobilities and emplacement. The paper considers what the ‘mobilities turn’ offers for understanding the geographies of education and our understanding of education and learning, with a focus on ripple effects, structures and subject positionings. Four different but related bodies of work are identified that productively engage a notion of ‘mobilities’ to challenge bounded conceptions of education through their focus on i) community and mobility; ii) ‘alternative’ spaces of education; iii) student mobilities; and iv) embedded institutional capital and internationalisation. Through the lens of mobilities, the paper advances research agendas within both geography (on ‘geographies of education’) and cognate disciplines (such as sociology and education).